Accuracy of Electrocardiography-guided PICC in Atrial Fibrillation Patients - Ibraheem Aljediea; Mohammed Alshehri; Khaled Alenazi; Amr Mimesh; Mustafa Fleet (The Arab Journal of Interventional Radiology)
Objectives We conducted this study to review our experience performing electrocardiography-guided peripherally inserted central catheter insertion in patients with atrial fibrillation. Materials and Methods This is a retrospective study of PICC insertions performed by interventional radiology technologists using electrocardiogram guidance in patients with atrial fibrillation. The study included 99 PICCs inserted using electrocardiography guidance in 79 patients diagnosed with atrial fibrillation. Chest X-ray is used to confirm tip position. Results We reviewed all PICCs inserted in patients with atrial fibrillation using electrocardiography guidance between September 2017 and June 2022. The review process included success and malposition rates using X-ray correlation. Ninety-four out of 99 PICCs were successfully inserted, and 5 cases required repositioning. Conclusion Our study suggests that electrocardiography navigation can be safely used for PICC insertion in patients with atrial fibrillation with high success rate.